2022
DOI: 10.3389/fcvm.2022.974345
|View full text |Cite
|
Sign up to set email alerts
|

Chronic intermittent hypoxia accelerates cardiac dysfunction and cardiac remodeling during cardiac pressure overload in mice and can be alleviated by PHD3 overexpression

Abstract: Obstructive sleep apnea (OSA) accelerates the progression of chronic heart failure (CHF). OSA is characterized by chronic intermittent hypoxia (CIH), and CIH exposure accelerates cardiac systolic dysfunction and cardiac remodeling in a cardiac afterload stress mouse model. Mechanistic experiments showed that long-term CIH exposure activated hypoxia-inducible factor 1α (HIF-1α) expression in the mouse heart and upregulated miR-29c expression and that both HIF-1α and miR-29c simultaneously inhibited sarco-/endop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 39 publications
(47 reference statements)
2
3
0
Order By: Relevance
“…However, Sano et al found that HIF-1α promotes cardiac vascularization and prevents cardiac hypertrophy and contractile dysfunction from occurring [14]. Our study showed that three months of CIH resulted in high HIF-1αexpression and a decrease in LV systolic function, which is consistent with the results of a national study [5], which suggested that short-term HIF-1α upregulation provides some benefits, while long-term HIF-1α high expression over eight weeks eventually leads to myocardial damage in rats. The expression of HIF-1α is elevated under hypoxia and translocates into the nucleus to be converted into HIF-1, which binds to various target genes in the nucleus to generate a hypoxia-induced response and promote the transduction of multiple signaling pathways [5].…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…However, Sano et al found that HIF-1α promotes cardiac vascularization and prevents cardiac hypertrophy and contractile dysfunction from occurring [14]. Our study showed that three months of CIH resulted in high HIF-1αexpression and a decrease in LV systolic function, which is consistent with the results of a national study [5], which suggested that short-term HIF-1α upregulation provides some benefits, while long-term HIF-1α high expression over eight weeks eventually leads to myocardial damage in rats. The expression of HIF-1α is elevated under hypoxia and translocates into the nucleus to be converted into HIF-1, which binds to various target genes in the nucleus to generate a hypoxia-induced response and promote the transduction of multiple signaling pathways [5].…”
Section: Discussionsupporting
confidence: 91%
“…Our study showed that three months of CIH resulted in high HIF-1αexpression and a decrease in LV systolic function, which is consistent with the results of a national study [5], which suggested that short-term HIF-1α upregulation provides some benefits, while long-term HIF-1α high expression over eight weeks eventually leads to myocardial damage in rats. The expression of HIF-1α is elevated under hypoxia and translocates into the nucleus to be converted into HIF-1, which binds to various target genes in the nucleus to generate a hypoxia-induced response and promote the transduction of multiple signaling pathways [5]. Wei et al found that the expression levels of HIF-1α, NF-κB, IL-6, and MMP2 were significantly elevated in the state of CIH, which triggered apoptosis, myocardial fibrosis, and diminished cardiac ejection capacity [15].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…CIH-induced ER stress contributes to HIF-1 activation (Belaidi, Thomas et al, 2016), and reciprocally, HIF-1 activation favours ER stress (Moulin, Thomas et al, 2020). Subsequent to HIF-1/ER stress activation, CIH alters mitochondria-associated ER membranes (Moulin et al, 2022), contributing to J Physiol 601.24 alterations in calcium handling, mitochondrial function and ultimately to myocardial apoptosis and cell death (Chen et al, 2010;Xu et al, 2022;Yeung et al, 2015). In contrast to this detrimental signalling induced by sustained and persistent HIF-1 activation, short-term exposure to moderate CIH induces HIF-1-dependent cardioprotective mechanisms (i.e.…”
Section: Mechanisms Involved In the Cardiac Response To Cihmentioning
confidence: 99%
“…Prolonged high glucose toxicity and multiple factors can induce overexpression of numerous cytokines, increased extracellular matrix production and deposition in the myocardial interstitium and perivascular areas, decreased myocardial compliance, and induced simultaneous ventricular diastolic dysfunction in late stages ( 2 , 53 , 54 ). Different promoter methylation has been reported in DCM.…”
Section: Dna Methylation Modifications and Dcmmentioning
confidence: 99%